PELATIHAN APLIKASI SOFTWARE GEOGEBRA DI SMP DAN SMK YAMAS DI JAKARTA - Bayu Jaya Tama; Sri Rezeki; Rahmawati Yuliyani (Pusat Riset dan Inovasi Nasional, 2022)
The use of information technology in the learning process can help visualize abstract concepts and be able to involve students' active roles in the learning process. The use of instructional media in the classroom is also an important component of the learning process in constructing basic mathematical concepts. The importance of using information technology in the learning process also has a positive impact on student motivation and learning outcomes. One form of application is the use of learning media using GeoGebra software. Through this Community Service (PKM) activity, the PKM team helps partners by providing training on the use of GeoGebra software. This training aims to make mathematics teachers more skilled in utilizing media in learning. This PKM activity was carried out in a demonstration, namely the PKM team first gave a seminar on GeoGebra software, then continued by providing training using GeoGebra software. With this, it is hoped that teachers can use GeoGebra software in the learning process.